PIMECROLIMUS APPLICATION IN TREATMENT FOR ATOPIC DERMATITIS DURING LOCALIZATION OF THE SKIN RASH IN AREAS WITH THIN AND SENSITIVE SKIN - O.V. Trusova; D.S. Korostovtsev ("Paediatrician" Publishers LLC, 2007)
The lecture highlights the modern approaches to the therapy for atopic dermatitis among children and adults, as well as reviews the principles of the external therapy prescription with regards to the localization of the rush on the patient's skin. The authors presents the most important findings of pimecrolimus clinical tests, including the information on the cream efficacy and tolerance if applied to the skin on the face and other parts with thin and sensitive skin. Key words: atopic dermatitis, children, adults, therapy, pimecrolimus.